Patterns of heart failure symptoms are associated with self-care behaviors over 6 months. (August 2018) - Auld, Jonathan P; Mudd, James O; Gelow, Jill M; Lyons, Karen S; Hiatt, Shirin O; Lee, Christopher S
Background: Both heart failure symptoms and self-care are associated with patient outcomes. Although it is thought that symptoms drive self-care, there is limited evidence to support this assumption over time. Aims: To determine whether patterns of physical symptoms are significantly associated with heart failure self-care over time. Method: Latent mixture analysis was used to identify subgroups based on physical symptoms of dyspnea, sleepiness and edema (using the heart failure somatic perception and Epworth sleepiness scales). Growth modeling was used to determine if symptom subgroups were associated with self-care behaviors (using the self-care in heart failure index) over 6 months. Sociodemographic and clinical variables predicting the likelihood of subgroup membership were identified using logistic regression. Results: The sample ( n =146) was on average 57 years old, 70% were men and 59% had class III/IV heart failure. Two symptom subgroups were identified (entropy 0.91): a high symptom group ( n =24; 16%) with no significant change in symptoms over time (high sustained), and a low symptom group ( n =122; 84%) with no significant change in symptoms over time (low sustained). The high sustained group was associated significantly with better self-care behaviors at baseline and over 6 months. Women (odds ratio (OR) 3.67, P =0.023) and patients with more depressive symptoms (OR 1.16, P =0.015) were more likely to be in the high sustained symptom group. Those treated with a renin–angiotensin–aldosterone system agent were less likely to be in the high symptom group (OR 0.17, P =0.015). Conclusion: Patients bothered more by symptoms are consistently more engaged in self-care behaviors over time. The results of this study support symptoms as an important driver of self-care behaviors.